The analysis of CO2 emissions and reduction potential in china's production and supply of electric and heat power industry: A case study based on the LMDI method. Issue 5 (19th March 2019) - Li, Wei; Liu, Liguo; Wang, Xuyang; Quan, Congxin; Zhang, Shu; Yu, Haiyong
Abstract : The Production and Supply of Electric and Heat Power Industry is an important energy supply sector in China. In this article, we apply the Logarithmic Mean Divisia Index decomposition method to analyze the carbon emissions of China's electricity and thermal supply industry from 2003 to 2012. Under different scenarios, this study also forecasts the carbon emissions and calculates reduction potential of The Production and Supply of Electric and Heat Power Industry. The results show the economic output effect and energy intensity effect promote the sector's CO2 emissions growth, however the energy structure effect decrease the sector's carbon emissions. At the end of 2030, the accumulated emission reduction will be 4160.84 Mt in moderate reduction scenario and 11, 593.27 Mt in strong reduction scenario. If all the indexes maintain the current change rate, the industry will reach carbon emissions peak at the time of 2030, What is more, the time for emissions peak will be 2025 and 2020 in moderate reduction scenario and strong reduction scenario. Finally, the article proposes to improve energy efficiency and promote the development of clean energy to reduce the carbon emissions of the Production and Supply of Electric and Heat Power Industry. Draw more stringent environmental standards and incentives to promote energy‐saving existing technology, the application can also combine with the means of financial subsidies to encourage the companies to reduce the energy intensity of the sector or strengthen the impact of energy intensity effect on the change of carbon emissions, promote the industry early peak. © 2019 American Institute of Chemical Engineers Environ Prog, 38:e13146, 2019